Customer satisfaction towards the service quality of internet banking in Standard Chartered / Raniza Abdul Razak - Abdul Razak, Raniza (2010)
This research was carried out to evaluate customer satisfaction towards the service quality of internet banking in Standard Chartered Bank. The problem that face by the company is to evaluate the level of customers’ satisfaction towards its internet banking since no face to face interaction exists in the business activities, making the evaluation harder. The first objective of this study is to determine level of customer satisfaction towards Standard Chartered internet banking. The second objective of this research is to determine customers’ perception on the internet banking service quality factors which are efficiency, reliability, responsiveness, fulfillment, and privacy. The last objective is to identify the relationships between service quality factors and customer satisfaction towards internet banking. This study was based on simple random sampling techniques by distributing 70 questionnaires to Standard Chartered internet banking customers in Technology Park Malaysia, Bukit Jalil. The overall findings of this research showed that customers are satisfied with the Standard Chartered internet banking with the average means for customer satisfaction is 3.8810. The service quality factors that have been measured are efficiency, reliability, responsiveness, fulfillment and privacy. Based on the respondents’ feedback, fulfillment and privacy are the factors that have the highest mean, with 3.9643 while efficiency is at the lowest with average mean, 3.5619. Based on the finding, it showed that there are positive relationships between efficiency, reliability, responsiveness, fulfillment, and privacy with customer satisfaction. Recommendation and suggestion on how to improve the service quality of the website have been identified to help Standard Chartered to increase customers’ satisfaction towards its internet banking.